The representation of a multimedia franchise as a single entity : contrasting existing bibliographic entities with web-based Superwork portrayals - Kiryakos, Senan (2021)
Background. Multimedia franchises may have a single origin, but over time develop into a network of related creative works in various media formats such as film, novels, animation, and video games. A single entity to represent a whole franchise is often utilized on the Web, but the ability for existing bibliographic models to represent this entity, which we refer to as the Superwork, is unclear. Objective. This research sought to determine whether entities representing multimedia franchises and the relationships they contain can be accurately portrayed using current models and, if not, how a new entity can be differentiated from the entities in the existing models. It also examines the role of existing franchise-level concepts on the Web and their ability to define properties and boundaries. Methods. We contrasted the franchise-level concept against official documentation and past research into similar entities (i.e. FRBR Work and FRBRoo Complex Work). A mapping and analysis of franchise articles on Wikipedia was performed to identify user-created boundaries and relationships between related instances. Results. The analysis revealed that the concept of a singular entity for a multimedia franchise was not the intended use for existing bibliographic entities, and that users will create such entities to collocate resources belonging to a single franchise. The Wikipedia mapping showed how and where users established relationships between works and media types, and thus what entities the Superwork should be directly connected to. Contribution. This study builds upon past bibliographic family and transmedia research, and suggests that more effort should be put towards examining existing collocation activities of users.